Service model based on lean tools to improve order fulfillment rate in a SMES in the commercial sector - Galarreta Bellido, Marina Elvira (2025)
The commercial sector has experienced steady growth in recent years. However, there are problems within logistics that are detrimental to customer satisfaction; the objective of companies is to deliver orders on time and minimize economic losses. That said, in this research, the problem that generates the greatest economic losses is the high percentage of unfulfilled orders. To address it, it is proposed to reduce this gap through a model based on Lean methodology, using methodologies such as 5S, ABC and Kanban, which allows improving the indicators. The research is based on internal logistics in a warehouse where the root causes of the problem are identified and quantified, and then attacked using Lean tools. Finally, through simulations with Arena software, it was demonstrated that the proposed model achieves a 38.8% reduction in picking time, 12.2% in system registration and 7.23% in total simulation time, which improves delivery compliance, reaching a target of 5% of unfulfilled orders.